Editorial [to] Indoor positioning and navigation part II: WSN and magnetic-based systems - Moreira, Adriano (2012)
Part I of the special issue on indoor positioning and navigation included a set of four papers, whose preliminary versions were presented at the IPIN 2011 conference, on indoor positioning systems based on fingerprinting techniques. This second part includes three other papers, two of them describing solutions based on magnetic sensors, and one paper describing a solution for positioning build around the IEEE 802.15.4 standard for wireless sensor networks.